A Robust Ru/ZSM‐5 Hydrogenation Catalyst: Insights into the Resistances to Ruthenium Aggregation and Carbon Deposition. Issue 19 (23rd August 2017) - Zhang, Bin; Wu, Qifan; Zhang, Chao; Su, Xinluona; Shi, Ruhui; Lin, Weiwei; Li, Yan; Zhao, Fengyu
Abstract: A long‐life topic in the field of heterogeneous catalysis has been to develop supported catalysts that are stable against the aggregation of active metal and carbon deposition. Herein, we report a highly stable Ru/ZSM‐5 catalyst for the hydrogenation of levulinic acid in water, which can be recycled at least 10 times without apparent loss of activity (conv. >95 %, yield >85 %). The influences of types of Al species, structure of support, Ru sizes, Ru leaching, and carbon deposition, etc. on activity and stability were discussed in detail. It was confirmed that the tetrahedral‐coordinated framework Al in ZSM‐5 contributed to the favorable metal–support interaction, and thus suppressed the aggregation and leaching of ruthenium during recycling. Besides, the suitable pore volume and channel network connectivity successfully prevent from deposition of carbonaceous residues. Abstract : Stability from the support : The excellent stability of a Ru/ZSM‐5 catalyst for levulinic acid hydrogenation in water relies on the higher tetrahedral‐coordinated Al content and preferable pore connectivity in well‐crystallized ZSM‐5 zeolite, which suppress Ru aggregation and leaching and the formation of carbonaceous residues in the acidic environment.